2024
DOI: 10.3390/s24020503
|View full text |Cite
|
Sign up to set email alerts
|

3D Road Boundary Extraction Based on Machine Learning Strategy Using LiDAR and Image-Derived MMS Point Clouds

Baris Suleymanoglu,
Metin Soycan,
Charles Toth

Abstract: The precise extraction of road boundaries is an essential task to obtain road infrastructure data that can support various applications, such as maintenance, autonomous driving, vehicle navigation, and the generation of high-definition maps (HD map). Despite promising outcomes in prior studies, challenges persist in road extraction, particularly in discerning diverse road types. The proposed methodology integrates state-of-the-art techniques like DBSCAN and RANSAC, aiming to establish a universally applicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Three-dimensional scanning, which encompasses technologies such as LiDAR, allows for detailed measurements and high-fidelity models, particularly with terrestrial setups where the equipment is stationary. For instance, a higher-resolution sensor influences the detection capabilities, distinguishing between different types of surfaces markings, obstacles, and traffic [95][96][97]. Conversely, the spatial resolution in Remote Sensing, which involves a broader range of technologies including aerial imagery and satellite photos, can vary significantly.…”
Section: Application Of Advanced Surveying Methods (Advanced Surveying)mentioning
confidence: 99%
“…Three-dimensional scanning, which encompasses technologies such as LiDAR, allows for detailed measurements and high-fidelity models, particularly with terrestrial setups where the equipment is stationary. For instance, a higher-resolution sensor influences the detection capabilities, distinguishing between different types of surfaces markings, obstacles, and traffic [95][96][97]. Conversely, the spatial resolution in Remote Sensing, which involves a broader range of technologies including aerial imagery and satellite photos, can vary significantly.…”
Section: Application Of Advanced Surveying Methods (Advanced Surveying)mentioning
confidence: 99%
“…Their study explicitly evaluated several training samples with different features and demonstrated a classification improvement of up to 13%. Suleymanoglu et al [30] introduced a methodology that combines techniques such as DBSCAN and RANSAC to extract road boundaries. This methodology was applied using 3D data from two distinct sources: MLS and a photogrammetry-based system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar comparisons were conducted for standard deviation as well. For the accuracy measure, the standard deviations of the glm, lda, [50] 0.9300 -Ha Tran and Taweep [26] -0.9740 Hanma et al [28] -0.9070 Zeybek and Biçici [51] -0.7300 Bai et al [52] 0.6941 0.8623 Biçici and Zeybek [25] 0.9500 -Wang et al [27] -0.9200 Suleymanoglu et al [30] -0.9390 This study (study area 1) 0.9720 0.9760 This study (study area 2) 0.9590 0.9690 and linda algorithms are found to be larger than those of the rf and svm algorithms. However, this observation is the opposite for the quality measure.…”
Section: Investigations On Other Study Areamentioning
confidence: 99%